2007
DOI: 10.1007/s00221-007-0850-2
|View full text |Cite
|
Sign up to set email alerts
|

Beta- and gamma-frequency coupling between olfactory and motor brain regions prior to skilled, olfactory-driven reaching

Abstract: A major question in neuroscience concerns how widely separated brain regions coordinate their activity to produce unitary cognitive states or motor actions. To investigate this question, we employed multisite, multielectrode recording in rats to study how olfactory and motor circuits are coupled prior to the execution of an olfactory-driven, GO/NO-GO variant of a skilled, rapidly executed (~350-600 ms) reaching task. During task performance, we recorded multi-single units and local field potentials (LFPs) simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…For instance, the observations reported here rely on theta-frequency synchrony, which is known to be prominent between the hippocampus and its targets. However, gamma-frequency synchrony can occur across functionally connected cortical regions (Hermer-Vazquez et al, 2007), raising the possibility that the method reported here may be of use in evaluating cortico-cortical functional connectivity if applied to this frequency range. Lastly, in the absence of candidate frequency bands it is possible to apply the amplitude cross-correlation method in successive frequency windows over a broad range, for example, from 1 to 100 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the observations reported here rely on theta-frequency synchrony, which is known to be prominent between the hippocampus and its targets. However, gamma-frequency synchrony can occur across functionally connected cortical regions (Hermer-Vazquez et al, 2007), raising the possibility that the method reported here may be of use in evaluating cortico-cortical functional connectivity if applied to this frequency range. Lastly, in the absence of candidate frequency bands it is possible to apply the amplitude cross-correlation method in successive frequency windows over a broad range, for example, from 1 to 100 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the olfactory oscillation bands, beta oscillations are most coherent across areas [55,5759] and occupy a very narrow frequency band centered about 20 Hz in mammals [60]. We know very little about the mechanisms of olfactory system beta oscillations, except that they require centrifugal input to the OB [39].…”
Section: Processes That Organize Activity and Link Olfactory Areasmentioning
confidence: 99%
“…The testing apparatus for the skilled task was made of clear Plexiglas with dimensions of 13.1 cm wide × 40 cm deep × 45 cm high (as in Whishaw and Pellis, 1990 and Hermer-Vazquez, 2008; Hermer-Vazquez et al, 2004, 2007a,b). The box stood on a plastic table with clean paper towels covering the floor for each rat.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a chimp did not fail to grasp a banana, yet still bring its hand to its mouth and begin chewing. Though it may seem surprising that we would even comment on this, in our extensive experience with rat motor skill and motor sequence learning (Hermer-Vazquez, 2008; Hermer-Vazquez et al, 2004, 2007a,b),we have often seen the animals perform such movements strangely out of order—indeed, including failing to grasp a pellet during a reaching task and yet bringing their reaching paw to their mouths, sometimes with subsequent chewing. Gharbawie, Whishaw and colleagues (Gharbawie et al, 2007; Gharbawie and Whishaw, 2006) have noticed some of the same tendencies of rats learning the same skilled reaching maneuver both before and after cortical injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation